Laser studies of plasmas - Jacobs, R; Jacobs, Robert (2000)
﻿ Measurement of the intrinsic properties of processing plasmas is critically important in understanding discharges so that the optimum conditions can be achieved. Several different diagnostic methods have been developed and tested. A planar probe has been used to measure the ion flux and electron temperature in both inductively coupled and capacitively coupled plasma systems, at various pressures and applied powers, using the assumption that the electron energy distribution is a Maxwellian. Frequency modulation spectroscopy (FMS) has been used to detect species in a plasma. It has been shown to be very effective, giving a significantly increased S/N ratio compared to both single pass absorption and low frequency mechanical modulation techniques. It has been used to measure excited argon atom concentrations, in both capacitively and inductively produced plasmas. The argon atom 4s[3/2]1 level concentration was found to be between 2 x 108 and 1 x 1011 atom/cm3 and to generally increase with increasing applied power and to decrease with increasing total pressure. The temperature of the atoms was also measured and was found to be approximately 323 ± 17 K. A simple compact laser source at 308 nm has been produced from a frequency doubled cooled commercial diode laser. This has been used to detect the OH radical, by absorption, within the afterglow of a microwave discharge, produced either directly or chemically. Simple kinetic models have provided explanations of the variations in OH concentration with discharge conditions. A novel method, cavity laser induced fluorescence (CLIP), that combines the advantages of both laser induced fluorescence (LIF) and cavity ring down spectroscopy CRDS, has been shown to increase the sensitivity of a diagnostic system compared to absorption. This method could be used to follow concentration variations of a reaction in a single laser shot. Although such variation can be observed using LIF, it requires a calibration and a many laser shot experiment with a signal recorded at each time point. Whilst CRDS allows temporal information about the absolute concentrations of the species observed to be obtained, it is not as sensitive as LIF. By combining the two in CLIP, it may be possible to retain the sensitivity of LIF with the advantage of CRDS so that absolute and time varying concentrations can be obtained in a single pulsed laser shot. LIF and CRDS signals have been observed using the A 2?u ? X 2Sg+ transition of the N2+ ion. The lifetime of the A 2?u state in the discharge was found to be sufficiently long for a time of flight experiment to be contemplated (an ion with a velocity of 10 kms-1 on average would travel 5 mm before radiating). Although the preliminary tests for the time of flight experiment have shown that this method is not feasible with a pulsed laser, the basic cavity locking procedures required for an analogous continuous wave experiment have been successfully demonstrated. A frequency doubled diode laser source has been constructed and tested, with the eventual aim of detecting N2+ via the B 2Su ? X 2Sg+ electronic transition. This has been found to be insufficiently intense to be used for a proposed two dimensional velocity mapping experiment, but several strategies to improve its performance are suggested.